Asteroseismological analysis of the ultra-massive ZZ Ceti stars BPM~37093, GD~518, and SDSS~J0840+5222 - Córsico, Alejandro Hugo (2019)
Ultra-massive hydrogen-rich (DA) white dwarfs (WD) are expected to have a substantial portion of their cores in a crystalline state at the effective temperatures characterizing the ZZ Ceti instability strip, as a result of Coulomb interactions. Asteroseismological analyses of these WDs can provide valuable information related to the crystallization process, the core chemical composition and the evolutionary origin of these stars. We present a thorough asteroseismological analysis of the ultra-massive ZZ Ceti star BPM~37093, which exhibits a rich period spectrum, on the basis of a complete set of fully evolutionary models that represent ultra-massive oxygen/neon(ONe)-core DA WD stars harbouring a range of hydrogen (H) envelope thicknesses. We also carry out preliminary asteroseismological inferences on two other ultra-massive ZZ Ceti stars that exhibit fewer periods, GD~518, and SDSS~J0840+5222. We found a mean period spacing of $Δ Π \sim 17$ s in the data of BPM~37093, associated to $\ell= 2$ modes. We found asteroseismological models for the three objects under analysis, two of them (BPM~37093 and GD~518) characterized by canonical (thick) H envelopes, and the third one (SDSS~J0840+5222) with a thinner H envelope. We also derive asteroseismological distances which are somewhat different to the astrometric measurements of {\it Gaia} for these stars. Asteroseismological analyses like the one presented in this paper could lead to a more complete knowledge of the processes occurring during crystallization inside WDs. Also, they could make it possible to deduce the core chemical composition of ultra-massive WDs, and in this way, to infer their evolutionary origin, i.e., if the star has a ONe core and then is the result of single-star evolution, or if it harbour a carbon/oxygen (CO) core and is the product of a merger of the two components of a binary system.